Perancangan Media Pembelajaran Biologi Berbasis Android di SMA Negeri 1 Kapur IX - Oktaviana ‎, Shania; Okra, Riri (Indonesian Research Journal on Education, 2023)
This research is motivated because teachers who teach Biology subjects in class X in deliveringsubject matter still use conventional media, such as printed books and still use the lecture method,causing many students to be unfocused and easily bored during class hours. ongoing. The source ofmaterial obtained by students is only obtained from the teacher and the module only, so that thematerial is not delivered optimally. The purpose of this study was to produce media for androidbased biology learning at SMA Negeri 1 Kapur IX using Adobe Flash CS6 software which was validand effective. In this study the method used is the Research and Development method with 4 stages.The research stages of 4D model development, this 4D model consists of defining, designing,developing, and disseminating. At this stage of the research, the the author collaborated the 4-Dversion of the RnD method and the multimedia development model of Luther-Sutopo. The product test results obtained validity, practicality and effectiveness tests, where the validity test was filled by 3 media expert lecturers obtained an average value of 0.80 which was declared valid, for the practicality test, 1 biology teacher author got an average an average of 0.92 with a very highcategory, and in the effectiveness test of five students class X with an average of 0.97 which wasdeclared very effective. the results of this biology learning media research in the form of an application that can be installed on the android of each student and teacher.